Transporting Mouse Embryos and Germplasm as Frozen or Unfrozen Materials. Issue 2 (16th June 2014) - Kenyon, Janet; Guan, Mo; Bogani, Debora; Marschall, Susan; Raspa, Marcello; Pickard, Amanda; Takeo, Toru; Nakagata, Naomi; Fray, Martin
Abstract: The 21st century has seen a huge proliferation in the availability of genetically altered mice. The availability of these resources has been accompanied by ever greater opportunities for international collaborations between laboratories involving the exchange of mouse strains. This exchange can involve significant costs in terms of animal welfare and transportation expenses. In an attempt to mitigate some of these costs, the mouse community has developed a battery of techniques that can be used to avoid transporting live mice. Transporting frozen embryos and sperm at liquid nitrogen (LN2 ) temperatures using dry shippers has been common practice for some time. However, current advances in this field have refined transportation procedures and introduced new techniques for disseminating embryos and sperm: for example, shipping frozen sperm on dry ice, exchanging unfrozen epididymides from which sperm can be extracted, and transporting frozen/thawed embryos in isotonic media. This article discusses some of the current practices used by laboratories to transport mouse strains around the world without having to exchange live mice. Curr. Protoc. Mouse Biol . 4:47‐65 © 2014 by John Wiley & Sons, Inc.